1995
DOI: 10.1177/0306624x9503900307
|View full text |Cite
|
Sign up to set email alerts
|

Rapists' Versus Non-Rapists' Attitudes Toward Women: A British Study

Abstract: Three groups (incarcerated rapists, incarcerated non-rapists and nonincarcerated controls) were administered and completed Parry's (1983) Anglicized version of Spence, Helmreich and Stapp's (1973) Attitudes Towards Women Scale. Results of the seventy-one subjects showed that the incarcerated non-rapist group held the most traditional/conservative attitudes towards women. The present findings are discussed in terms of feminist viewpoint, current sociopolitical issues and cross-Atlantic research differences in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…In other words, self-serving definitions of deviant social behaviour may ease the cognitive discomfort produced by the offending behaviour. The strength of the behaviourÁ cognition relationship observed in the sexual offender group in this study is important as previous research had difficulty in discriminating this type of offender from other types in terms of some cognitive variables (Harmon, Owens, & Dewey, 1995;Marolla & Scully, 1986).…”
Section: Normative Beliefs and Crime Involvementmentioning
confidence: 81%
“…In other words, self-serving definitions of deviant social behaviour may ease the cognitive discomfort produced by the offending behaviour. The strength of the behaviourÁ cognition relationship observed in the sexual offender group in this study is important as previous research had difficulty in discriminating this type of offender from other types in terms of some cognitive variables (Harmon, Owens, & Dewey, 1995;Marolla & Scully, 1986).…”
Section: Normative Beliefs and Crime Involvementmentioning
confidence: 81%
“…Although no distinction was made between adult-oriented and child-oriented sex offenders in the primary analysis, subsequent analyses showed that the groups did not differ on any of the attitude measures. In a British study by Harmon, Owens, and Dewey (1995), rapists were found to have less traditional attitudes toward the role of women in society than other imprisoned offenders. No attitudinal differences were found between rapists and a nonoffender control group.…”
Section: Attitudes and Beliefsmentioning
confidence: 97%
“…A number of studies have been unable to statistically discriminate rapists from various offender and community comparison groups (see Harmon, Owens, & Dewey, 1995;Sattem, Savells, & Murray, 1984). Marolla and Scully (1986) and Bumby (1996) have reported some of the only findings hinting that rapists' cognitions may be different from comparison groups.…”
Section: Cognitive Productsmentioning
confidence: 99%